Pemanfaatan Limbah Tulang Ikan Kurisi (Nemipterus nematophorus) Sebagai Sumber Kalsium dalam Sediaan Crackers - Tiara, Najwa Mega; Purgiyanti, Purgiyanti; Riyanta, Aldi Budi (Jurnal Kesehatan Rajawali, 2024)
The growing consumption of fish among the public has resulted in significant growth in the fishing industry, causing uncontrolled disposal of production waste. One type of waste from the fishing industry is fish bones, which can be used to make flour. Flour derived from Kurisi fish bones has a high calcium and phosphorus content compared to other calcium sources. The aim of this research is to determine the potential of Kurisi fish bone waste as a source of calcium in cracker preparations and to determine the determination of water content and ash content in cracker preparations using the water content and ash content testing method as well as calcium testing. This research was carried out using qualitative methods for organoleptic testing and calcium levels, as well as quantitative methods for testing the water content and ash content of Kurisi fish bone crackers. Based on research data, it shows that kurisi fish bone waste can be processed into fish bone meal for making crackers. This represents the conversion of waste into valuable products, reducing waste and increasing resource efficiency. The addition of Kurisi fish bone meal affects the water content, ash content, and sensory quality of the crackers (color, aroma, shape, taste). In making these crackers, the best treatment was obtained for the F1 sample, namely the addition of 10% Kurisi fish bone flour.